If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + -30 = 9 + -11n Reorder the terms: -30 + 2n = 9 + -11n Solving -30 + 2n = 9 + -11n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '11n' to each side of the equation. -30 + 2n + 11n = 9 + -11n + 11n Combine like terms: 2n + 11n = 13n -30 + 13n = 9 + -11n + 11n Combine like terms: -11n + 11n = 0 -30 + 13n = 9 + 0 -30 + 13n = 9 Add '30' to each side of the equation. -30 + 30 + 13n = 9 + 30 Combine like terms: -30 + 30 = 0 0 + 13n = 9 + 30 13n = 9 + 30 Combine like terms: 9 + 30 = 39 13n = 39 Divide each side by '13'. n = 3 Simplifying n = 3
| 5x-y=-10 | | 20a-14=0 | | 23-x=2x-22 | | 3X^2=18-25X | | 2n-30=11n | | 3u-3=-12 | | (x^2)-9= | | -3x-2=7x+4 | | 100=2.5x | | 5z=60 | | 1.6q-3.5-5.2q=-4.6q-5.4 | | 4x+10=x+3(3x+3)+1 | | 12x^2+41x+24=0 | | 5x+29y=-19 | | 2(n+2)=3n+9 | | x*6+47=x*11-8 | | x^3-70x^2+1500x-10800=0 | | 5(y-1)=7(3+y) | | 18x^2-9x-20=0 | | b^2+3=5b-3 | | 58-6x=3x+19 | | x^2+36=100 | | 8-2a=2 | | -3-2(y+4)=3y-(4y-5) | | 12x^2+43x+36=0 | | 5(2x+n)=2(n-1) | | 47=-62 | | 10x+6x= | | 29+18=-59-3 | | 3x=5y+2 | | 3(2x-1)=11-x | | 4y-4=6-7y |